2022
DOI: 10.3389/fphys.2022.874321
|View full text |Cite
|
Sign up to set email alerts
|

Thriving in Oxygen While Preventing ROS Overproduction: No Two Systems Are Created Equal

Abstract: From 2.5 to 2.0 billion years ago, atmospheric oxygen concentration [O2] rose thousands of times, leading to the first mass extinction. Reactive Oxygen Species (ROS) produced by the non-catalyzed partial reduction of O2 were highly toxic eliminating many species. Survivors developed different strategies to cope with ROS toxicity. At the same time, using O2 as the final acceptor in respiratory chains increased ATP production manifold. Thus, both O2 and ROS were strong drivers of evolution, as species optimized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 171 publications
(211 reference statements)
0
3
0
Order By: Relevance
“…In this study, the authors reported that when KCN was added first, it partially inhibited mitochondrial oxygen consumption (in our case, mitochondrial reductive capacity, Figure 2b), and was completely inhibited after adding octyl-gallate. As mentioned previously [41,42], oxyconformers present branched mitochondrial respiratory electron chains. Together with the well-known mitochondrial oxidative phosphorylation (OxPhos) components, other redox enzymes are present as alternative oxidases (AOX), which, as mentioned above, are inhibited by other molecules such as octyl-gallate [35].…”
Section: Discussionmentioning
confidence: 53%
“…In this study, the authors reported that when KCN was added first, it partially inhibited mitochondrial oxygen consumption (in our case, mitochondrial reductive capacity, Figure 2b), and was completely inhibited after adding octyl-gallate. As mentioned previously [41,42], oxyconformers present branched mitochondrial respiratory electron chains. Together with the well-known mitochondrial oxidative phosphorylation (OxPhos) components, other redox enzymes are present as alternative oxidases (AOX), which, as mentioned above, are inhibited by other molecules such as octyl-gallate [35].…”
Section: Discussionmentioning
confidence: 53%
“…However, straightforward augmentation of oxygen supply in the constructs will not yield a sustainable general solution because high concentrations of oxygen (hyperoxia) can inadvertently lead to ROS overproduction 34 (Fig. 3 ).…”
Section: The Pivotal Role Of Oxygen In Mammalian Eventsmentioning
confidence: 99%
“…Trained lizards exhibited lower resting metabolic rates and lower maximal mitochondrial respiratory capacity than controls, indicating differing whole-organism and mitochondrial adaptations in response to higher energy demands from exercise training. Individual mitochondria can respond to demands by adjusting activity within the electron transport chain such as proton concentrations contributing to proton-motive force across the inner mitochondrial membrane, which affects ATP synthesis, proton leak, and ROS production (Treberg et al, 2018;Koch et al, 2021;Mendez-Romero et al, 2022). When oxygen consumption is uncoupled from ATP synthesis, individual mitochondria found within different organisms can have similar OCR with very different ATP synthesis rates (Koch et al, 2021).…”
Section: Mitochondria Function-mito Stress Testmentioning
confidence: 99%